Land use/land cover changes in the period of 2015–2020 in AngYai Village, Sikhottabong District, Vientiane Capital, Lao PDR - Thien, Bui Bao; Sosamphanh, Bounthavy; Yachongtou, Bounheuang; Phuong, Vu Thi (Geology, Geophysics and Environment, 2022)
In this study, land use/land cover (LULC) changes were identified in AngYai Village, Sikhottabong District, Vientiane Capital, Laos, from 2015 to 2020 using the Geographic Information System (GIS) and remote sensing (RS). Topographic maps and Google Earth Pro satellite imagery data were used with ArcGIS 10.8 software to map land use fluctuations. The study area was classified into the six main types of LULC (agricultural, builtup, forest, main roads, waste land, and water bodies) based on field research, geographical conditions, and RS data. The results indicated sizeable increases in the built-up, main roads, and especially waste land areas over the study period. The forest and agricultural land areas decreased during the study period, possibly due to increased urbanization rates, nomadic cultivation, and indiscriminate deforestation in the study area. The river area was affected by the construction of hydroelectric dams and by the climate, leading to the drying up of water sources and causing water body areas to decrease to some extent.